PELAYANAN RUJUKAN PADA BAYI BARU LAHIR DENGAN ASFIKSIA - Trida Nova Rina; Lusi Andriani; PS. Kurniawati PS. Kurniawati (Poltekkes Kemenkes Bengkulu, 2020)
Abstract: From 2016 to October 14 cases of infant mortality from 397 treated with asphyxia deaths. This study aims to find out about referral services, referral handling groove BBL asphyxia cases in hospitals and quality of care in referral hospitals Rejang Lebong. Population and sample are all new born mothers with asphyxia reconciled to Curup General hospital 17 peopleTo that end, used a qualitative approach with case study method. The results showed the village midwife already handle asphyxia newborns up with the first step and Positive Pressure Ventilation, but the reference is often delayed because of the inhibiting factors of the family (the economy and the decision to refer should involve a large family) and environmental factors (transportation). As a result hospitals and related institutions need to consider the skills and knowledge of the officers by including officers for NICU and PICU neonatal residential training and for the village midwifwe management training asphyxia.Keywords: Referral Services, Asphyxia, Newborn.